Innovative development management network enterprises in the context of increasing the efficiency of financial and economic activity - Petrova, І.; Петрова, І.; Viktorov, B.; Вікторов, Б.; Zakharchyn, G.; Захарчук, Г.; Bondarchuk, Natalia; Бондарчук, Наталія Володимирівна; Melnyk, T.; Мельник, T. (Banking University Lviv, 2021)
For the network enterprises under research, the acquisition, organization of application of technologies, programmes, equipment which will improve economic, market, technical indicators, will provide the possibility to increase the general level of innovation has been suggested. To ensure the optimal selection, the use of innovative platforms for the selection of technologies, programmes, equipment has been proposed. Its application provides the possibility to identify the needs of innovative development of each of the enterprises under research and to develop individualized areas of innovation. The purpose of the article is to identify key problems of innovative development of Ukrainian network enterprises and to develop ways to improve its management on the basis of promising technologies. The methodology of assessing the state of innovative development of enterprises on the basis of four groups of indicators, namely the financial ones, the impact of innovative capacity on the level of international business development, staff composition, and logistics system, which has been implemented for five network structures on their primary information base, is presented. The expediency of adapting the Polish experience regarding the use of an innovative selection platform, which provides simulation modelling of the implementation of technologies and programmes, to the conditions and features of Ukrainian networks has been proved. Only network enterprises and their management system and innovative development were considered. The use of algorithms for commercialization of technologies, software that will allow the staff of research units of network structures to identify individualized needs of innovative development and develop individualized areas of innovation of the network structure, thus ensuring greater efficiency of innovation has been proposed. The results of the assessment made it possible to identify the main problems of innovation in network enterprises. Анотація. Для досліджуваних мережних підприємств запропоновано придбання, організація застосування технологій, програм, обладнання, які покращать економічні, ринкові, технічні показники, дадуть можливість підвищити загальний рівень інноваційності. Для забезпечення оптимального відбору запропоновано використання інноваційних платформ для відбору технологій, програм, обладнання. Його застосування дає можливість визначити потреби інноваційного розвитку кожного з досліджуваних підприємств та розробити індивідуальні напрямки інновацій. Метою статті є визначення ключових проблем інноваційного розвитку українських мережевих підприємств та розробка шляхів удосконалення управління ним на основі перспективних технологій. Впроваджено методологію оцінки стану інноваційного розвитку підприємств на основі чотирьох груп показників, а саме фінансових, впливу інноваційного потенціалу на рівень розвитку міжнародного бізнесу, склад персоналу та логістичну систему. представлено п'ять мережевих структур на їх первинній інформаційній базі. Доведено доцільність адаптації польського досвіду щодо використання інноваційної платформи відбору, яка забезпечує імітаційне моделювання впровадження технологій та програм, до умов та особливостей українських мереж. Розглядалися лише мережеві підприємства та їх система управління та інноваційний розвиток. Запропоновано використання алгоритмів комерціалізації технологій, програмного забезпечення, що дозволить співробітникам науково-дослідних підрозділів мережевих структур визначати індивідуалізовані потреби інноваційного розвитку та розвивати індивідуалізовані напрями інноваційної структури мережі, забезпечуючи тим самим більшу ефективність інноваційної діяльності. Результати оцінки дозволили визначити основні проблеми інноваційної діяльності на мережевих підприємствах.
Управління Інноваційним розвитком мережевих підприємств в контексті підвищення ефективності фінансово-економічної діяльності
Keywords: innovative development; інноваційний розвиток; simulation modelling; імітаційне моделювання; intellectualization; інтелектуалізація; network interaction; мережева взаємодія; network enterprises; мережеві підприємства